Regional distribution of DXA-measured body fat mass in athletes with a locomotor impairment - Cavedon, V.; Zancanaro, C.; Milanese, C. (8th International Congress Mountain Sport & Health. Updating Study and Research from Laboratory to Field. 7-8 November 2019, Rovereto (TN) - Italy. Programme and Book of Abstracts, 2019)
Introduction. In athletes with a locomotor impairment, the use of anthropometric predictive equations to assess body composition is of limited use because of their low accuracy. A satisfactory explanation for such a drawback is not available. A possible factor is an altered body distribution of fat mass (FM) in this athletic population and/or the presence of body asymmetry. This hypothesis was tested by assessing regional %FM in 52 athletes with a locomotor impairment (wheelchair-bound [WB; n = 25] and walkers [Walk; n = 27]) in comparison each with an age- and %FM-matched group of able-bodied athletes (AB). Methods. Whole-body and regional (upper limbs, lower limbs and trunk) %FM was assessed in all participants by means of Dual-Energy X-ray Absorptiometry. The independent-samples T-test was used to evaluate differences in the regional distribution of %FM between WB and Walk and their respective AB control group. A mixed-design 4 x 2 Analysis of Variance (ANOVA) with group (WB, Walk and their respective AB) and body side (right and left) as the factors was performed to assess group by side interaction for %FM in the appendicular regions. If a significant interaction was detected, post-hoc pairwise comparisons with Bonferroni correction were carried out. In the case of impairment predominantly affecting one lower limb, the non-affected lower limb was considered as "right" while the affected lower limb was considered as "left". Results. %FM in the trunk region was similar between the two groups of athletes with a locomotor impairment and their respective control group. The WB group had significantly lower (-5.5%, P = 0.01) %FM in the upper limbs vs. the corresponding AB group, while the Walk group had similar %FM in the upper limbs vs. the corresponding AB group. Both groups of athletes with a locomotor impairment had higher (+8.5%, P = 0.001 and +4.9%, P = 0.01, respectively) %FM in the lower limbs vs. their respective AB group. In the lower limbs, ANOVA showed a significant main effect of group x side interaction for %FM (F = 11.01, P<0.001). Post hoc analysis revealed that %FM was significantly lower (-7.9%, P<0.001) in the nonaffected versus the affected side in the Walk group only. Conclusions. These results prompt for the development of population-specific anthropometric equations in order to more accurately estimate body composition in athletes with a locomotor impairment.